2019
DOI: 10.3390/w11071416
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Arcobacter and Other Pathogenic Bacteria in River Water in Nepal

Abstract: This study aims to determine the diversity of pathogenic bacteria in the Bagmati River, Nepal, during a one-year period. A total of 18 river water samples were collected from three sites (n = 6 per site) along the river. Bacterial DNA, which were extracted from the water samples, were analyzed for bacterial 16S rRNA genes by next-generation sequencing for 13 of 18 samples, and by quantitative PCR targeting Arcobacter for all 18 samples. The 16S rRNA sequencing identified an average of 97,412 ± 35,909 sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…As reported previously [11,12], 100-mL river water samples were collected in sterile bottles once every 2 months between November 2015 and September 2016 from Sundarijal (upstream), Thapathali (midstream), and Chovar (downstream), as shown in Figure 1. Land cover usage details on the map were based on a previously conducted study [14].…”
Section: Sample Collection and Extraction Of Bacterial Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…As reported previously [11,12], 100-mL river water samples were collected in sterile bottles once every 2 months between November 2015 and September 2016 from Sundarijal (upstream), Thapathali (midstream), and Chovar (downstream), as shown in Figure 1. Land cover usage details on the map were based on a previously conducted study [14].…”
Section: Sample Collection and Extraction Of Bacterial Dnamentioning
confidence: 99%
“…It flows from north to south in the Kathmandu Valley, passing through the densely populated region. Previous studies have reported a degraded microbiological quality of water and showed that the Bagmati River is a reservoir of pathogenic bacteria, viruses, and protozoa [10][11][12]. However, studies regarding the detection of clinically relevant ARGs and MGEs have not been published.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they also found Arcobacter cryaerophilus, as the predominant species in the river. This species has been reported as very frequent in other rivers such as the Yangtze (China) [37], many rivers in Nepal [38], and the Llobregat (Spain) [39]. As mentioned before, Arcobacter is an emergent enteropathogen and indicator of fecal contamination.…”
Section: Discussionmentioning
confidence: 73%
“…Arcobacter cryaerophilus, the predominant species in the Lower Rimac, has been reported as very frequent in other rivers such as the Yangtze (China) [49], many rivers in Nepal [52], the Llobregat (Spain) [53], and the Pinheiros river [14]. As mentioned before, Arcobacter is an emergent enteropathogenic bacterium and an indicator of fecal contamination.…”
Section: Discussionmentioning
confidence: 85%